KINERJA UNIT PELATIHAN INDUSTRI KECIL MENENGAH DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI KALIMANTAN BARAT - Herita E.21110029, Ethy (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
Research on training unit small and medium industries department of industry and commerce west Kalimantan province there is a related phenomenon with performance which demonstrates not yet maximum. That in view of the there indicators, namely the aspectÂ  Productivity, Quality Service and Responsiveness. On produktivitas still not optimal, visible energy fields so that did not suit the job is not done effectively and efficient. The quality of coaching and traning services, training unit small and medium industries have not been able to reach all districts are widely, so as to provide a little late. Subsequent responsiveness as indicated by the alignment between services and needs the capabilities are still not effective, so as to respond in accordance with the needs of training is not optimal. Purpose of study is investigate the performance of small and medium industrial training unit department of industy and commerce west Kalimantan province. Researchers in this study used a qualitative approach with descriptive research. Conclusions from the results of this study shows that the productivity of service quality and responsiveness in carrying out its duties and functions are still some low so that the impact on performance is still not optimal. Researchers eventually gave her recommendations to the training unit small and medium industries department of industry and commerce west Kalimantan province expected to further improve human resource, improving educations and skills possessed, and improve facilities and infrastructure, that are expected to work effectively and better and able to perform the duties and functions well and correctly.Â Keyword: performance small and medium industrial training unit, Productivity, Quality Service and Responsiveness